SELF-MENTIONS IN APPLIED LINGUISTICS RESEARCH ARTICLES WRITTEN BY INDONESIANS AND NON-INDONESIANS - Slamet Utomo; Fitri Budi Suryani (Universitas Stikubank (UNISBANK) Semarang, 2019)
This study explores self-mentions in Applied Linguistics research articles written by Indonesians and non-Indonesians. Twenty research articles consisting of 10 research articles written by Indonesians, and the other 10 by non-Indonesians were randomly selected from the leading and international Applied Linguistics journal published in 2017-2018. The use of first person pronouns in those articles was recorded and analyzed. The results indicate the more frequent use of self-mentions in the research articles written by Indonesians than by non-Indonesians. However, the use of first person plural pronoun is higher in the research articles written by non-Indonesians.